The importance of environmental education in vectors monitoring in a rural community Uberlândia, MG: opportunities and challenges - Oliveira, João Carlos de; Lima, Samuel do Carmo; Silva, Arcênio Meneses da; Carvalho, Neuza Aparecida R. (Revista Hipótese, 2017)
This work is part of environmental education activities in the prevention of dengue in a rural community of Uberlândia (MG), coordinated by the Technical Courses Environmental Control and Environment (ESTES/UFU), in partnership with Medical Geography Laboratory (IG/UFU), Federal Institute of Education, Science and Technology (IFTM) and the Municipal School “Sobradinho”.
Keywords: Ovitrap surveys; Community Mobilization; Environmental Education; Dengue